The Economic Empowerment of Women in Uganda Through Mushroom Production - Ibarahim Mayanja; Tolga Tipi (Turkish Journal of Agriculture: Food Science and Technology)
This study focuses on empowering women both in peri-urban and rural areas through mushroom production. It was conducted in Kampala Metropolitan area-Uganda, during October 2016. It focused on estimating profits, conducting benefit-cost analysis/ratio (BCR) and return on investment (ROI), finding reasons as to why women involved in the mushroom production and identifying the constraints of mushroom farming from the perspective of women as well as the possible solutions to the constraints. 29 women were interviewed face to face through the use of the questionnaires. The study revealed an average net profit of 3,464.28 US dollars, BCR of 3.84 and ROI of 2.84 per farm in a period of three months. Our study revealed that mushroom production is a profitable enterprise for women. The major reason for women to involve in mushroom was to earn income. However, a range of other reasons was given such as fast maturity of mushrooms, availability of market, healthy benefits of mushrooms, etc. were the most important reasons. The problems faced by women farmers were ranked from the most pressing problem to the least pressing problem in this order; Low market prices per kilogram of mushroom, scarcity of cotton during some seasons, poor quality mushroom spawn supplied to farmers by breeders, inadequate extension, and advisory services were the most observed problems among others. The suggested solutions were organizing farmers into groups or cooperatives in order to negotiate for better markets locally and abroad together with the help of government, researchers to carry out more research on the suitability of other substrates like bagasse other than relying on only cotton, ensuring that mushroom spawn breeders conform to the set standards of quality spawn production and re-equipping local extension workers with knowledge regarding mushroom production among others.